Genome-wide CRISPR screen identifies RACK1 as a critical host factor for flavivirus replication - Shue, Byron; Chiramel, Abhilash I.; Cerikan, Berati; To, Thu-Hien; Frölich, Sonja; Pederson, Stephen M.; Kirby, Emily N.; Eyre, Nicholas S.; Bartenschlager, Ralf; Best, Sonja M.; Beard, Michael R. (Journal of virology, 2021)
Cellular factors are critical in all facets of viral lifecycles, where overlapping - interactions between the virus and host can be exploited as possible avenues for the - development of antiviral therapeutics. Using a genome-wide CRISPR knockout screening - ...
Gesehen am 02.03.2022